Analisis Proses Blanking dengan Simple Press Tool - Rizza, Muhammad Akhlis (Jurnal Rekayasa Mesin, 2014)
Blanking production process will be required for mass production due to good product quality and lower production costs. For mini wrench products, blanking process can be done with a simple press tool. This analysis starting with design, manufacturing and than analysis. It’s concluded that the construction of simple press tool are Plate Material (ST 60), Pillar Material (ST 60), Punch and Dies Material (SKD 11 with 15 mm thickness and 0.108 mm clearance), stripper material (ST 37), the punch holder material (ST 37), and the stopper material (ST 37). Forces acting on the machine press tool are cutting force (37 kN), clamping force (371 N), and power press machine (8.5 kW).Keywords: Blanking, press tool